Analisis Determinan Faktor pada Earning Per Share Perusahaan - Asteria, Beta; Riauwanto, Selamet (Universitas Batanghari, 2024)
Research aimed to analyze the effect of profitability and solvency to earnings per share. EPS describes the firm’s performance. Whether the firm’s performance is good or not, one of which is measured by its ability to generate profit per share. Also the presence of research gaps from previous research. This makes this research interesting and urgent to do. This research is used purposive sampling method. The samples criteria are included in the LQ45 Index, have positive EPS, have positive profitability and have complete data needed in this research. Research data were analyzed through the Linear Regression program. Regression analysis is carried out by conducting the t test and F test. T test is carried out to analyze the effect of each independent variable on the dependent variable and F test is carried out to analyze the effect of the independent variables simultaneously on the dependent variable. Based on the t test, the results show that Return on Equity or profitability at a significance of 0.000 <0.05 and the Solvency variable at a significance of 0.001 <0.05 proves to have a significant effect on Earnings Per Share (EPS). Based on the F test, it shows the results of profitability and solvency have simultaneous significant effect on Earnings Per Share (EPS) at a significance of 0.001 <0.05.